8D.09: NIGHTTIME HYPOTENSIVE EFFECTS OF CENTRAL ANGIOTENSIN II TYPE 2 RECEPTOR STIMULATION THROUGH IMPROVED SPONTANEOUS BAROREFLEX SENSITIVITY. (June 2015) - Brouwers, S.; Wainford, R.D.; Smolders, I.; Dupont, A.G.
Abstract : Objective: The angiotensin II type 2 receptor (AT2R) has been suggested to counterbalance the angiotensin II type 1 receptor (AT1R) in the central regulation of blood pressure and sympathetic tone. We previously reported the decrease in mean arterial pressure (MAP) to selective stimulation of central AT2R with Compound 21 (C21) in conscious spontaneous hypertensive rats (SHR) and normotensive Wistar Kyoto rats (WKY). Here we show the differences in day- and nighttime pressure. We also assess the impact on spontaneous baroreflex sensitivity (SBRS), norepinephrine (NE) plasma levels and autonomic function. Design and method: Animals were implanted with a radio-telemetry device and an intracerebroventricular cannula connected to a miniosmotic pump delivering saline vehicle, AT2R-agonist C21 alone or in combination with AT2R-antagonist PD123319. MAP was assessed for 14–21 days: 7 days baseline (saline), 7–14 days treatment (e.g. C21) (n = 6–8/group). Results: During daytime, 7-day C21-infusion decreased MAP similarly in the two strains (WKY -5.5 ± 0.6 mmHg, SHR -5.4 ± 1.5 mmHg). During nighttime, C21 reduced MAP significantly more in SHR (-12.6 ± 1.9 mmHg) than in WKY (-8.2 ± 0.8 mmHg;p < 0.01). In SHR, the nighttime hypotensive response was significantly greater than during daytime both after 7 (p < 0.05) and 14 (p < 0.001) days; a similar trend was seen in WKY. SBRS, on day 2 and day 7 of baseline period, was significantly impaired in SHR compared to WKY (SBRS (ms/mmHg): WKY D2 2.6 ± 0.3, D7 2.5 ± 0.4; SHR D2 2.0 ± 0.1, D7 1.8 ± 0.2;both p < 0.05). C21-infusion immediately increased SBRS significantly in both strains; this effect was maintained throughout the infusion period (SBRS(ms/mmHg): WKY D9 3.6 ± 0.3, D14 3.7 ± 0.4;both p < 0.01 vs baseline; SHR D9 3.2 ± 0.2, D14 3.4 ± 0.2, D21 3.7 ± 0.1;all p < 0.01 vs baseline). The improvement in SBRS on D14 was more pronounced in SHR than in WKY (84 vs 46%;p < 0.001). Co-infusion of PD123319 abolished these effects. C21 significantly decreased NE plasma levels and attenuated the bradycardic response to ip bolus propranolol. Conclusions: Chronic stimulation of central AT2R with C21 lowers MAP through sympatho-inhibition in WKY and SHR. The improvement in SBRS and the hypotensive effect during nighttime is more pronounced in SHR than in WKY. Central AT2R-stimulation could open new therapeutic opportunities in hypertension or diseases characterized by sympatho-excitation.